Nazhir, Cash Waqf, and Digitalization: Assessing Sharia Compliance and Governance at Laznas Yakesma Kepri - Pratama, Agung; Ummah, M. Fijar Ishlahul; Amar, Rizki; Wahidy, Sultan (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: Cash waqf has become an increasingly significant instrument in supporting social and economic development in Indonesia. Laznas Yakesma of the Riau Islands is among the institutions engaged in the collection and management of cash waqf. This study aims to analyze the governance of cash waqf at Laznas Yakesma Kepri by evaluating the gap between the fulfillment of sharia objectives and adherence to national positive law. The research specifically assesses the extent to which nāẓir practices correspond with the principles of maqāṣid al-sharī‘ah, particularly ḥifẓ al-māl, and examines avenues for strengthening governance models to ensure alignment with the prevailing legal framework. A qualitative approach with a descriptive-analytical design is utilized. Primary data were collected through observation and semi-structured interviews with nāẓir representatives, while secondary data were sourced from waqf regulations as well as academic literature. Findings indicate that Yakesma Kepri has maintained the integrity of the waqf’s principal value, developed funds productively via a catering business, and disbursed resulting benefits to beneficiaries. These practices are indicative of the application of ḥifẓ al-māl and the socio-economic objectives of Islamic law. Nonetheless, inconsistencies remain regarding positive legal requirements, notably the lack of official certificates from Islamic financial institutions, insufficient protection via Islamic insurance, and limited digital systems and reporting to BWI. This study recommends enhanced collaboration between nāẓir, Islamic financial institutions, and Islamic insurance companies, together with the development of digital systems for fundraising, reporting, and transparency in cash waqf management. An integrated governance model is anticipated to foster more modern, accountable, and sustainable cash waqf management. Abstrak: Wakaf uang memainkan peran yang semakin penting dalam mendorong pembangunan sosial dan ekonomi di Indonesia. Salah satu lembaga yang aktif dalam penghimpunan dan pengelolaan wakaf uang adalah Laznas Yakesma Kepulauan Riau. Penelitian ini bertujuan untuk menganalisis tata kelola wakaf uang di Laznas Yakesma Kepri dengan menyoroti kesenjangan antara pencapaian tujuan syariah dan kepatuhan terhadap hukum positif nasional. Fokus kajian diarahkan pada sejauh mana praktik nāẓir sejalan dengan prinsip maqāṣid asy-syarī‘ah, khususnya ḥifẓ al-māl, serta bagaimana model tata kelola dapat diperkuat agar sesuai dengan kerangka hukum yang berlaku. Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif-analitis. Data primer diperoleh melalui observasi dan wawancara semi-terstruktur dengan pihak nāẓir, sedangkan data sekunder bersumber dari peraturan perundang-undangan wakaf serta berbagai literatur akademik. Hasil penelitian menunjukkan bahwa Yakesma Kepri telah berhasil menjaga keutuhan nilai pokok wakaf, mengembangkan dana secara produktif melalui usaha katering, dan menyalurkan hasilnya kepada penerima manfaat. Praktik tersebut mencerminkan implementasi prinsip ḥifẓ al-māl dan tujuan sosial-ekonomi syariah. Namun, masih terdapat sejumlah ketidaksesuaian dengan ketentuan hukum positif, antara lain belum diterbitkannya sertifikat resmi oleh Lembaga Keuangan Syariah, belum adanya perlindungan melalui asuransi syariah, serta keterbatasan sistem digital dan pelaporan kepada BWI. Penelitian ini merekomendasikan perlunya penguatan kolaborasi antara nāẓir, Lembaga Keuangan Syariah, dan perusahaan asuransi syariah, disertai pengembangan sistem digital dalam proses penghimpunan, pelaporan, dan transparansi pengelolaan wakaf uang. Model tata kelola yang terintegrasi ini diharapkan dapat mewujudkan pengelolaan wakaf uang yang lebih modern, akuntabel, dan berkelanjutan.